2022
DOI: 10.1021/acs.chemrestox.2c00160
|View full text |Cite
|
Sign up to set email alerts
|

Methylglyoxal and Its Adducts: Induction, Repair, and Association with Disease

Abstract: Metabolism is an essential part of life that provides energy for cell growth. During metabolic flux, reactive electrophiles are produced that covalently modify macromolecules, leading to detrimental cellular effects. Methylglyoxal (MG) is an abundant electrophile formed from lipid, protein, and glucose metabolism at intracellular levels of 1–4 μM. MG covalently modifies DNA, RNA, and protein, forming advanced glycation end products (MG-AGEs). MG and MG-AGEs are associated with the onset and progression of many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 358 publications
1
53
0
Order By: Relevance
“…The results indicated that GKM3- and GKK2-fermented supernatants significantly inhibited MG-induced ketoamine production in the early stage of the in vitro MG-BSA glycation model ( p < 0.05) ( Figure 1 ). MG can modify amino residues, specifically lysine and arginine, generating adducted amino residues, which can further result in protein cross-linking and the formation of macromolecules in the late stage of protein glycation [ 2 ]. In the present study, MG-induced protein cross-links can be found in the late stage of the in vitro MG-BSA glycation model as evidenced by the graphs of SDS-PAGE ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results indicated that GKM3- and GKK2-fermented supernatants significantly inhibited MG-induced ketoamine production in the early stage of the in vitro MG-BSA glycation model ( p < 0.05) ( Figure 1 ). MG can modify amino residues, specifically lysine and arginine, generating adducted amino residues, which can further result in protein cross-linking and the formation of macromolecules in the late stage of protein glycation [ 2 ]. In the present study, MG-induced protein cross-links can be found in the late stage of the in vitro MG-BSA glycation model as evidenced by the graphs of SDS-PAGE ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Argpyrimidine is an MG-derived advanced glycation end product (AGE), which is implicated in aging-related cognitive dysfunction [ 30 ] and other disorders [ 2 ]. Gomes et al found a high concentration of argpyrimidine in the patients with familial amyloidotic polyneuropathy, a neurologic disease [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond the reactive enals and ene-dicarbonyls such as respectively HNE and DMF, as discussed above, native reactive electrophilic molecules, such as methylglyoxal or 15-deoxy-Δ (12,14)-prostaglandin J₂ (15d-PGJ₂)-nature's small molecules playing functional roles in various disease-relevant biological processes-constitute additional classes of native reactive electrophiles, where gaining a comprehensive picture of how these electrophiles form functional covalent complexes with their target proteins, could prove helpful. [69][70][71] A couple of crystal structures of 15d-PGJ₂protein complexes have been reported, although we did not include them here as our discussion was restricted to native reactive electrophiles of 200 Da or less. [72][73][74] On the other hand, and to the best of our knowledge, no structural data exist for the non-Michael-acceptor-based electrophile methylglyoxal-bound proteins.…”
Section: Capturing Structural Data On Kinetically-privileged Electrop...mentioning
confidence: 99%
“…MGO-derived AGEs have been shown to play a pivotal role in the onset and progression of vascular complications of diabetics. Methylglyoxal thus appears to be a significant contributor to endothelial dysfunction by increasing oxidation, as well as inducing inflammation and apoptosis [ 1 , 2 , 3 , 4 ]. Therefore, MGO scavenging and glycation inhibition are now recognized as promising therapeutic targets in diabetes, pre-diabetes, and early prevention of hyperglycemic complications.…”
Section: Introductionmentioning
confidence: 99%